Examination of pediatric tube feeding schedules and oral intake: A retrospective cross-sectional study - Waddle, Caitlin; Gillespie, Scott E (Nutrition in clinical practice, 2023)
A common treatment goal for children dependent on enteral feeding is to advance oral nutrition intake and decrease enteral feeding dependence. The purpose of this study was to investigate the relationship between tube feeding schedule and oral intake in feeding tube-dependent children diagnosed with avoidant restrictive food intake disorder (ARFID). A retrospective chart review was completed including 76 tube-dependent children with ARFID between the ages of 1 and 14 years who were evaluated by a registered dietitian, in conjunction with a multidisciplinary feeding team, during January 1, 2018, to May 31, 2019. Eligible participants were diagnosed with ARFID and receiving enteral nutrition via nasogastric or gastrostomy tube during the time of evaluation. The participants were categorized into groups according to tube feeding schedule type (bolus vs. overnight continuous) and further stratified by severity of oral motor deficit, as documented by the speech language pathologist or occupational therapist: none/mild and moderate/severe. The exclusion criteria included children aged <1 year, appetite stimulant listed as an active medication, overnight enteral feeding infusion of >12 h, or calculated percentage of calories from oral intake not specified. The primary study outcome was dichotomized percentage of oral intake, >0% vs 0%. Following adjustment for confounders, this retrospective chart review showed statistically higher odds of percentage of oral intake >0% in ARFID patients receiving overnight continuous enteral feeding schedules (odds ratio = 0.20, 95% CI: 0.05-0.83, P = 0.027). A bolus feeding schedule may not promote oral intake in feeding tube-dependent children diagnosed with ARFID.